Parental Involvement in the Educational Transition of Students with Intellectual and Developmental Disabilities: From Secondary School to Vocational Pathways - Kushwaha, Ravindra Kumar (CV. Rayyan Dwi Bharata, 2025)
The transition from secondary education to vocational pathways is a critical phase in the lives of students with Intellectual and Developmental Disabilities (IDD), demanding multi-level support systems to ensure successful outcomes. Among these, parental involvement stands out as a crucial determinant of effective and sustainable transition planning. This study explores the perceptions, experiences, and challenges faced by parents as they support their children with IDD through this educational and vocational shift. Drawing upon Bronfenbrenner’s Ecological Systems Theory and the framework of Family-Centered Transition Planning (FCTP), the research investigates individual, institutional, and systemic factors influencing parental engagement. It addresses four central questions: how parents perceive their roles and responsibilities, the barriers they encounter, the institutional mechanisms that facilitate or hinder involvement, and strategies for enhancing collaboration between families, schools, and vocational institutions. The study highlights that while policies like IDEA (U.S.) and the Rights of Persons with Disabilities Act (India) recognize the role of families, practical implementation remains inconsistent. Findings from existing literature underscore the need for improved communication, cultural responsiveness, and interagency coordination to empower parents effectively. Many parents feel unprepared, excluded, or overwhelmed, particularly in under-resourced or rural contexts. Conversely, when provided with clear information, respect, and opportunities for participation, they contribute meaningfully to the development of individualized transition plans (ITPs). This research calls for inclusive educational practices, enhanced teacher training, and policy reforms that recognize parents as equal partners. Strengthening parental involvement is essential not only for the empowerment of families but also for the long-term vocational success of students with IDD.